Sistema para el manejo de datos de Ensayos Clínicos XAVIA SIDEC. - Vega Izaguirre, Leodan; Quintana Díaz, Victor Manuel; Tamayo Peña, Rafael; Dominguez Izquierdo, Yackelyn Dayanys; Molina Hernández, Yenisel (Revista Cubana de Informática Médica)
Clinical trial is the method used to evaluate a product, substance, medicine, diagnostic or therapeutic technique. The biotechnology industry employs clinical trial management systems to achieve efficient management of data collected during clinical trials. CIM (Centro de Inmunología Molecular) uses the Clinical Trials Management System XAVIA Clínicas developed by UCI, to support 100% of clinical trials since 2012. This system has limitations in its functionalities; furthermore, based on the experience obtained, improvements and new functionalities were identified, so it was decided to develop a new version of the system. The objective of this article is to present the Clinical Trials Data Management System XAVIA SIDEC and its generalization in BioCubaFarma institutions. The bibliography referring to the clinical trial data management and electronic data collection notebooks was studied and homologous systems available in the international market were analyzed. The development methodology used was AUP-UCI. Eclipse was used as an integrated development environment, Java as a programming language, JBoss as an application server and PostgreSQL as a database management system. The Clinical Trials Data Management System XAVIA SIDEC facilitates and makes the Case Report Forms (CRF) design and approval more flexible, standardizes the information handled, validates the data collected through rules, improves the flow of information between the entities conducting the trial and optimizes the monitoring process.